A Nodes Scheduling Approach for Effective Use of Gateway in Dense LoRa Networks - Kumari P.; Gupta H.P.; Dutta T. (My University, 2025)
Long Range (LoRa) is a wireless communication technology which enables Internet of Things (IoT) devices to efficiently and robustly communicate over long distances with low power consumption. The LoRa supports six Spreading Factors (SFs) and therefore a limited number of virtual channels are possible at a given time instance. Such limited number of channels restate the simultaneous use of a LoRa Gateway (LG) by the large number of LoRa Nodes (LNs) in a dense LoRa network and create the bottleneck problem at the LG. The bottleneck problem reduces the proper use of the allocated SFs and the utility of the LNs. In this paper, we propose a game theoretic approach that allocates the time duration to the LNs in the network for accessing the SFs. Such time duration maximizes the utility of the LNs in the network. The time duration determined on different SFs are then scheduled to minimize the waiting time of LNs. The proposed approach is validated by simulating the LoRa network using Network Simulator-3. Our simulations show that the proposed approach effectively reduces the waiting time and prolongs the network utility. © 2020 IEEE.